Congenital tracheoesophageal fistula: An anesthetic challenge (Indian Journal of Case Reports, 2024)
Managing a patient scheduled for congenital tracheoesophageal fistula (TEF) repair is challenging for the anesthetist. If an appropriate ventilation strategy is not employed, serious complications such as hypoxemia, gastric distension, and pulmonary aspiration can occur. We present the case of a 2-day-old male child, suffering from an isolated TEF without esophageal atresia (type H) scheduled for an open surgical repair performed by transthoracic approach (right thoracotomy). We successfully managed this intervention and herein report this case to demonstrate the multiple pre-operative, intraoperative, and post-operative complications regarding intubation that can occur while managing such a case.